A bibliometric analysis on the relationship between the use of Lean tools and 4.0 technologies on the product development process - Tardio, Paulo Roberto; Nara, Elpidio Oscar Benitez; Schaefer, Jones Luís (Brazilian Journal of Production Engineering, 2023)
The Product Development Process (PDP) takes place and depends on a series of integrated steps, incorporating different technologies and adapting to production standards. In this sense, the use of Lean tools can help to continuously improve processes in a systematic way, ensuring that all these processes really add value to the product. Allied to this, the implementation of Industry 4.0 technologies can help improve these production processes, enabling companies to obtain competitive advantages. Therefore, this research aims to map, correlate and analyze the existing scientific knowledge on PDP, Industry 4.0 and Lean Manufacturing. For this, searches will be carried out to retrieve articles from the Scopus database, and the data will be processed with the bibliometrix software. The results obtained show that there is a greater proximity between PDP and Lean Manufacturing, connected a priori and with a later connection with Industry 4.0. With this, it is possible to affirm that researchers and managers have a view that Lean tools are directly connected to the PDP, continuously helping for its success, while Industry 4.0 technologies are usually considered in a second moment regarding the execution of the PDP.